2004
DOI: 10.1158/0008-5472.can-04-0679
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell-Like Features of Testicular Carcinoma in Situ Revealed by Genome-Wide Gene Expression Profiling

Abstract: Carcinoma in situ (CIS) is the common precursor of histologically heterogeneous testicular germ cell tumors (TGCTs), which in recent decades have markedly increased and now are the most common malignancy of young men. Using genome-wide gene expression profiling, we identified >200 genes highly expressed in testicular CIS, including many never reported in testicular neoplasms. Expression was further verified by semiquantitative reverse transcription-PCR and in situ hybridization. Among the highest expressed gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
217
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(231 citation statements)
references
References 41 publications
11
217
0
3
Order By: Relevance
“…Ectopic expression of Nanog leads to dedifferentiation and blocks further developmental processes (Taranger et al, 2005). Malignant transformation of teratocarcinomas and germline tumors are caused by ectopic expression of Nanog (Almstrup et al, 2004;Hoei-Hansen et al, 2005;Skotheim et al, 2005). Overexpression of the full-length retrogene Nanog P8 has been identified in a large variety of different solid tumors or cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of Nanog leads to dedifferentiation and blocks further developmental processes (Taranger et al, 2005). Malignant transformation of teratocarcinomas and germline tumors are caused by ectopic expression of Nanog (Almstrup et al, 2004;Hoei-Hansen et al, 2005;Skotheim et al, 2005). Overexpression of the full-length retrogene Nanog P8 has been identified in a large variety of different solid tumors or cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…These markers are now commonly used in the clinical setting to help identify CIS in surgical biopsies. More recently, the expression profiles of CIS cells studied by microarrays (Almstrup et al, 2004;Skotheim et al, 2005) provided a series of candidate marker genes, such as TFAP2C (AP2γ) (Hoei-Hansen et al, 2004), which has shown promising results as a possible marker of CIS cells in semen samples (Hoei-Hansen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells have been isolated from adult mouse testes that exhibit properties similar to ES cells (Guan et al, 2006;Seandel et al, 2007), and these studies showed that a subset of spermatogonial stem cells in mouse testes retain the embryonic phenotype of PG cells and gonocytes. In humans a different scenario is seen, where NANOG and OCT3/4 (together with KIT and AP2γ) are expressed in PG cells and gonocytes, but are downregulated during the second half of pregnancy and until 2-4½ months of post-natal age (Jorgensen et al, 1995;Rajpert-De Meyts et al, 2004;Hoei-Hansen et al, 2004;Honecker et al, 2004;HoeiHansen et al, 2005). During this early infantile period, a transient increase in the production of testicular hormones occurs, known as the 'mini-puberty ' (Forest et al, 1973), which coincides with Page 6 of 22 A c c e p t e d M a n u s c r i p t 6 the final stage of differentiation of gonocytes into infantile spermatogonia (Hadziselimovic et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, tumors of types a, c, and d are composed of differentiated tissues, whereas type b GCTs demonstrate pluripotent potential. A close resemblance between testicular GCTs and embryonic stem (ES) cells has been shown [4]. Specific expression of Oct 3/4 has been related to the pluripotent capacity of testicular GCTs, suggesting their origin from transformed pluripotent progenitor cells, such as PGCs [100].…”
Section: Ovarian Cancer: Pluripotency and Putative Cscsmentioning
confidence: 99%
“…Despite differential histology, seminomas and IGCNU share a high overlap of gene expression with ES cells [4,20,21]. Pluripotency genes such as Oct 3/4 and Nanog are highly expressed in IGCNU, seminomas, and embryonal carcinomas, but not in other histological types of TGCTs.…”
Section: Human Testicular Gctsmentioning
confidence: 99%